IMPROVING STUDENTS' PUBLIC SPEAKING SKILLS THROUGH RHETORIC COURSES AND DA'WAH PRACTICUM - Heri Rahmatsyah Putra; Fadhlur Rahman Armi; Rahmi Rahmi Rahmi (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2022)
AbstractThe ability to communicate in front of the audience is one of the standard skills that must be possessed by students of the Islamic Communication and Broadcasting (KPI) study program. To obtain this ability, it is necessary to have effective communication implemented by lecturers in rhetoric/public speaking courses and da'wah practicum. Through this research, the writer wants to know the level of students' public speaking skills and the implementation carried out by lecturers in improving public speaking skills and da'wah practicum for KPI study program students. This study uses qualitative methods with data collection through observation, interviews, and documentation. In accordance with the results of the study, there is no effective communication between lecturers and students in improving students' public speaking competence. In addition, there are still many factors that cause the weakness of public speaking skills of KPI study program students.Keywords: Effectiveness, Rhetoric, Da'wah Practicum, Competence